(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
The genus Monochoria is represented in Sri Lanka by only two species, M. hastata and M. vaginalis. Of the two species M. vaginalis exhibits a high morphological diversity. A morphometric analysis was performed on the Sri Lankan members of the genus Monochoria to evaluate the morphological diversity exhibited by comparing 34 vegetative, anatomical and reproductive characters. Both cluster and principal coordinate analyses resulted in four clusters of which one corresponded to M. hastata, while M. vaginalis was divided into three phenetic groups indicating that the Sri Lankan M. vaginalis is a species complex involving more than one taxon. The length ratio of the lower spathe petiole to inflorescence stalk was identified as an informative character in delimiting the phenetic groups, a character that has not been considered before. Further, the occurrence of sub-palisade cavities that are filled with a red colored liquid in the leaves of two phenetic groups was a novel character for the genus as well as the family Pontederiaceae. Keywords: Monochoria vaginalis; Morphological data; Sub-palisade cavities; Principal coordinate anaysis. Bangladesh J. Plant Taxon. 24(1): 1322, 2017 (June)